Analisis Kualitas Hidup Pasien Diabetes Melitus Tipe 2 Berdasarkan Pola Peresepan Antidiabetik dan Komplikasi - Pande Made Desy Ratnasari; Tri Murti Andayani; Dwi Endarti (Faculty of Pharmacy, Universitas Gadjah Mada)
Type 2 diabetes mellitus (T2DM) is a chronic metabolic disease that requires lifelong therapy to control blood glucose. The long term use and different mechanism of action antidiabetic have the potential cause side effects and discomfort that affects the quality of life. This study aimed to determine differences in the quality of life of patients with T2DM based on antidiabetic prescribed and complications at the Outpatient of Panembahan Senopati Bantul Yogyakarta Hospital in September 2017. This research is observational with a cross-sectional design. Quality of life data is taking concurrently using the Diabetes Quality of Life Clinical Trial Questionnaire and patient's medical record. This study involved 200 T2DM patients who received antidiabetic at least 3 months before study, aged ≥18 years and agreed to inform concent. Sociodemographic data, antidiabetic prescribed and complications were described descriptively. Differences in the quality of life based on antidiabetic prescribed and complications using the Kruskal Wallis test which was further analyzed using the post hoc by Mann Whitney test. The results showed the majority of patients received oral combination with insulin (48.5%) and dominated by macrovascular complications (19.5%). The average value of patient's quality of life is 65.7. There was difference quality of life based on antidiabetic prescribed in the domain of treatment satisfaction (p=0.000) between oral monotherapy with combination of oral and insulin (p=0.000) and insulin monotherapy with combination of oral and insulin (p=0.002). There were differences in quality of life based on complications in the mental health domain (p=0.003) between macrovascular and microvascular (p=0.011) and between microvascular and without complications (p=0.001).